2005
DOI: 10.3171/sup.2005.102.s_supplement.0114
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient gamma knife surgery for vestibular schwannoma: definition of the therapeutic profile based on a 10-year experience

Abstract: Object. The purpose of the study was to define the therapeutic profile of outpatient gamma knife surgery (GKS) for vestibular schwannoma (VS) by using sequential tumor volumetry to quantify changes following treatment. Methods. A total of 111 patients met the inclusion criteria. The median follow-up duration was 7 years (range 5–9.6 years). Thirty-seven patients (33%) had undergone surgery before GKS and 10 (9%) had neurofibromatosis Type 2 (NF2). The median VS volume was 1.6 cm3 (range 0.08–8.7 cm3). The actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…A meta-analysis of the tumor control rates in 3677 patients from 37 recently published studies reported an overall local control rate of 91.1% (95% confidence interval, 90.4-93.7) [26]. Recently, gamma knife facilities have reported tumor control rates of 87-98.5% [5,[27][28][29]. This is largely consistent with the 88.6% tumor control rate observed at the final MRI in our study.…”
Section: Tumor Volume Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…A meta-analysis of the tumor control rates in 3677 patients from 37 recently published studies reported an overall local control rate of 91.1% (95% confidence interval, 90.4-93.7) [26]. Recently, gamma knife facilities have reported tumor control rates of 87-98.5% [5,[27][28][29]. This is largely consistent with the 88.6% tumor control rate observed at the final MRI in our study.…”
Section: Tumor Volume Controlsupporting
confidence: 93%
“…The incidence of this transient growth pattern has been reported to range from 3% to 80% [5,8,9,16,25,[29][30][31][32][33][34], and one reason for this disparity is thought to be the method for evaluating enlargement. It is necessary to determine whether tumors that enlarge early after treatment will continue to grow or instead begin to shrink.…”
Section: Tumor Volume Change Patterns and Peaks In Transient Tumor Vomentioning
confidence: 95%
“…In an arbitrary selection of 10 papers 4,6,9,[11][12][13]20,21,28,31 published since 2000 in which the treatment of vestibular schwannoma by GKS was described, prescription isodoses varied between 30% and 94%, 4,20 although some centers (in three of 10 papers) reported strict adherence to the 50% isodose line, 12,13,21 and one group reported strict adherence to the 65% isodose line. In an arbitrary selection of 10 papers 4,6,9,[11][12][13]20,21,28,31 published since 2000 in which the treatment of vestibular schwannoma by GKS was described, prescription isodoses varied between 30% and 94%, 4,20 although some centers (in three of 10 papers) reported strict adherence to the 50% isodose line, 12,13,21 and one group reported strict adherence to the 65% isodose line.…”
Section: Optimal Isodosesmentioning
confidence: 99%
“…On the other hand, the tumor may recur, especially in NF2 patients and when reduced doses are used (20). Moreover, tardive malignant transformation may occur, especially in young and/or NF2 patients, but this eventuality is widely overlooked (21).…”
Section: Discussionmentioning
confidence: 96%